Governance Models and Stunting: Comparative Policy Insights from Indonesia, Malaysia, and Mexico - Dwiputrianti, Septiana; Balian, Moch. Ubaidillah; Arshad, Rozita; Kadelbach, Vivian; Abdullah, Sait (Pusjar SKPP Lembaga Administrasi Negara, 2025)
162 million children worldwide are affected by stunting, which has serious societal repercussions (WHO, 2021). In order to identify institutional drivers of success, this study compares the governance styles used to address stunting in Mexico (hybrid), Malaysia (centralised), and Indonesia (decentralised). Through a qualitative examination of 45 coverage documents (2015–2023) and 72 stakeholder interviews, we find that Malaysia's NPAN uses cross-regional cooperation to reduce stunting by 12%, while Indonesia's bureaucratic fragmentation hinders implementation. The importance of network engagement is emphasized in Mexico's PENSAN application. By showing how adaptive frameworks that are adapted to local capacities improve fitness outcomes, the study advances the idea of collaborative governance. Malaysia is a prime example of a collaborative governance model that involves a fewstakeholders and improves its national nutrition strategy. Mexico's comprehensive strategy, which combines health and social regulations, underscores the significance of community engagement in public health initiatives. A comparative analysis of stunting incidence indicates that Indonesia (20.0%) and Malaysia (24.3%) face significant challenges in reducing stunting rates, whereas Mexico (13.9%) has made greater progress in this area. This study gives contribution to the study of public administration by illustrating how centralized (Malaysia), decentralized (Indonesia), and hybrid (Mexico) governance systems influence the effectiveness of health interventions. It provides critical insights for policymakers and practitioners, advocating for inclusive stakeholder participation and the necessity of context specific solutions. This study redefines discussions on decentralization in global health governance and fills the gap on cross-national governance analyses in stunting policy. This study indicates that policymakers ought to promote institutional flexibility and participatory design to attain SDG objectives.